2014
DOI: 10.1080/10610278.2014.924626
|View full text |Cite
|
Sign up to set email alerts
|

Tuning supramolecular G-quadruplexes with mono- and divalent cations

Abstract: Supramolecular G-quadruplexes (SGQs) are formed via the cation promoted self-assembly of guanine derivatives into stacks of planar hydrogen-bonded tetramers. Here, we present results on the formation of SGQs made from the 8-(m-acetylphenyl)-2′-deoxyguanosine (mAGi) derivative in the presence of various mono- and divalent cations. NMR and HR ESI-MS data indicate that varying the cation can efficiently tune the molecularity, the fidelity and stability (thermal and kinetic) of the resulting SGQs. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 57 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…Experimentally, however, we have only identified one type of dodecamer in solution. 18, 2122, 37, 3940 Such experimental evidence also strongly suggests that the observed 3 T-SGQ results from the stacking of a third tetrad on a pre-existing D 4 -symmetric 2 T-SGQ. Therefore, we can deduce that the dodecamer formed must have at least one homomeric interface ( hh or tt ), which were the ones selected for further MDS studies (Scheme 1).…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Experimentally, however, we have only identified one type of dodecamer in solution. 18, 2122, 37, 3940 Such experimental evidence also strongly suggests that the observed 3 T-SGQ results from the stacking of a third tetrad on a pre-existing D 4 -symmetric 2 T-SGQ. Therefore, we can deduce that the dodecamer formed must have at least one homomeric interface ( hh or tt ), which were the ones selected for further MDS studies (Scheme 1).…”
Section: Resultsmentioning
confidence: 78%
“…This is energetically costly because of its stabilizing effect due to the ion dipole interactions with the O6 of the guanine moiety. 37, 53 Consequently, an empty assembly should result in greater electrostatic repulsion among the carbonyls aligned at the central cavity of the tetrad resulting in significantly less stable SGQs. Although a number of computational studies have suggested that empty tetrads could be stabilized by - interactions and bifurcated H-bonds, 5455 the tt 2 T-SGQ ( n T-SGQ: 2 , 3 ) show none of those interactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations